2020
DOI: 10.3390/cells9061524
|View full text |Cite
|
Sign up to set email alerts
|

Flow Induced Symmetry Breaking in a Conceptual Polarity Model

Abstract: Important cellular processes, such as cell motility and cell division, are coordinated by cell polarity, which is determined by the non-uniform distribution of certain proteins. Such protein patterns form via an interplay of protein reactions and protein transport. Since Turing’s seminal work, the formation of protein patterns resulting from the interplay between reactions and diffusive transport has been widely studied. Over the last few years, increasing evidence shows that also advective transport, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Biochemical reactions are also modulated by physical processes such as fluid flows, which may happen in the cytosol and at the membrane. In large metazoan cells, cytoskeletal-driven cortical and cytosolic fluid flows, causing advective protein movements, play important roles in cell polarization ( 5 ) and can, in principle, promote polarity establishment ( 6 ). Membrane flows are predicted to occur and equilibrate membrane tension between spatially segregated zones of exo- and endocytosis, such as in tip growth of walled pollen tubes ( 7 , 8 ) or in cell migration, as initially proposed in ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical reactions are also modulated by physical processes such as fluid flows, which may happen in the cytosol and at the membrane. In large metazoan cells, cytoskeletal-driven cortical and cytosolic fluid flows, causing advective protein movements, play important roles in cell polarization ( 5 ) and can, in principle, promote polarity establishment ( 6 ). Membrane flows are predicted to occur and equilibrate membrane tension between spatially segregated zones of exo- and endocytosis, such as in tip growth of walled pollen tubes ( 7 , 8 ) or in cell migration, as initially proposed in ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This differential flow-induced propagation has been theoretically studied for two-component mass-conserving reaction diffusion models. 44 There, it was shown that flow drives the upstream propagation of patterns that are stationary in the absence of flow.…”
Section: Resultsmentioning
confidence: 99%
“…The same holds true for the influence of advective flow on biological pattern formation, which has rarely been studied, both experimentally and theoretically. 16,27,40,42,5052 Insight into the detailed biochemical mechanisms of the MinD-MinE interactions (such as cooperative MinD self-recruitment, dimerization of MinD and MinE, MinE membrane binding, etc.) is likely needed to make progress.…”
Section: Discussionmentioning
confidence: 99%
“…A number of models have been developed to understand properties of the PAR signaling network. These models are typically partial differential equation models that capture the diffusion, biochemical reactions, and transport due to flow in the system (Aras et al, 2018; Dawes and Iron, 2013; Geßele et al, 2020; Goehring et al, 2011; Gross et al, 2018; Kravtsova and Dawes, 2014; Seirin-Lee et al, 2020; Wigbers et al, 2020). Goehring et al (2011) for example found that a wave-pinning like mechanism (Holmes and Edelstein-Keshet, 2016; Holmes et al, 2012a,b, 2017; Jilkine and Edelstein-Keshet, 2011; Jilkine et al, 2007; Lin et al, 2012; Marée et al, 2006; Mata et al, 2013; Mori et al, 2008; Zmurchok and Holmes, 2020) may be responsible for stabilization of the anterior-posterior border.…”
Section: Introductionmentioning
confidence: 99%